The conceptualization of dress in prophetic metaphors - Parrott, S. J. (Supplements to Vetus Testamentum, 2023)
While the last four years has seen a renewed interest in dress in biblical studies, much of this work focuses on dress as object —what it is, looks like, and who wears it. In consequence, the symbolic and rhetorical function of dress in metaphors is often reduced to its function in “real life.” In response, this study bridges the conversation from what dress is to what dress is doing . By focusing on dress as subject and a concept, this study identifies constellations that hold prophetic metaphors of the investiture/divestiture of dress together with respect to identity formation/deformation, suffering, and destruction